Evaluación de hormonas comerciales enraizadoras en estaquillas axilares y apicales para la propagación vegetativa de (Duranta erecta) - Miño Peñafiel, Jenniffer Silvana (2022)
The cultivation of ornamental plants is an activity that, due to its production and marketing characteristics, is closely related to agricultural activity. In general, the nurseries that produce ornamental plants can be divided into two fields, indoor and outdoor. They tend to specialize in one of two areas, since each requires different resources to develop each type